Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Kinerja Karyawan (Studi Kasus Pada Kantor Camat Wera-NTB) (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study was to determine the effect of emotional intelligence and spiritual intelligence on employee performance. The method used in this research is a quantitative method based on the philosophy of positivism. The sampling technique used was saturated samples. The population and sample used were 72 employees. The data analysis method used in this research is quantitative method, namely the process of simplifying the data into a form that is simple to read. The results of this study provide empirical evidence that the variables of emotional intelligence and spiritual intelligence both simultaneously and partially have a positive and significant effect on employee performance. Keywords: Emotional intelligence, spiritual intelligence, employee performance